Suicide of the elderly: the fragilized tie with the desire of being alive (Research, Society and Development, 2020)
This study brings considerations about the suicide of the elderly, seeking to inform aspects related to aging, as well as what is suicide and the possible reasons why the number of elderly people who commit this act is increasing considerably. In this way, we seek to sensitize society - whose knowledge about this theme is little or nonexistent - about the need to demystify the theme and have a more sensitive and welcoming look, carrying out effective and preventive actions with regard to suicide. Through the literature review in the academic Google, Pepsic and Scielo databases, it is possible to understand its multifactorial aspects, as well as to identify the intervention and prevention strategies that psychology uses in order to contribute to the management of suicide cases, attempts and ideations. Various studies support this theme by offering discussions about old age, suicide and the role of psychology in the therapeutic context. Intervention and prevention strategies should be promoted through access to health, therapeutic monitoring and social actions that assist in the insertion of the elderly in the community, in addition to rescuing bonds and family support. Depression and other diseases, addictions, retirement, neglect, are some of the factors identified as causes of suicide among the elderly population. The elderly need healthy bonds, care strategies, access to health and the maintenance of their rights for a dignified quality of life in this stage of life.